2021
DOI: 10.14814/phy2.14872
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol consumption on flow‐mediated dilation in humans: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…A recent meta-analysis confirmed that long-term, heavy drinking is associated with abnormal FMD. 82 Fourth, the increased oxidative stress related to alcohol use has been shown to promote the generation of 20-hydroxyeicosatetraenoic acid (20-HETE), another vasoconstrictor. 80,[82][83][84] Fifth, alcohol directly causes release of endothelin-1 and endothelin-2 from vascular endothelial cells, further contributing to the vasoconstrictorvasodilator imbalance.…”
Section: Chronic Alcohol-related Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis confirmed that long-term, heavy drinking is associated with abnormal FMD. 82 Fourth, the increased oxidative stress related to alcohol use has been shown to promote the generation of 20-hydroxyeicosatetraenoic acid (20-HETE), another vasoconstrictor. 80,[82][83][84] Fifth, alcohol directly causes release of endothelin-1 and endothelin-2 from vascular endothelial cells, further contributing to the vasoconstrictorvasodilator imbalance.…”
Section: Chronic Alcohol-related Hypertensionmentioning
confidence: 99%
“…82 Fourth, the increased oxidative stress related to alcohol use has been shown to promote the generation of 20-hydroxyeicosatetraenoic acid (20-HETE), another vasoconstrictor. 80,[82][83][84] Fifth, alcohol directly causes release of endothelin-1 and endothelin-2 from vascular endothelial cells, further contributing to the vasoconstrictorvasodilator imbalance. 85 Finally, alcohol-induced dysregulation of calcium cycling in vascular smooth muscle cells has been described, impairing vascular relaxation.…”
Section: Chronic Alcohol-related Hypertensionmentioning
confidence: 99%
“…Therefore, alcohol-induced arterial stiffening may be related to endothelial dysfunction. Along with this possibility, our recent systemic review suggests that heavy alcohol consumption (≥ 3–5 drinks, daily or binge pattern) is associated with a decrease in brachial artery flow-mediated dilation [ 57 ], a non-invasive measure of endothelial function in humans.…”
Section: Mechanisms Of Alcohol-associated Changes In Arterial Stiffeningmentioning
confidence: 99%
“…Endothelial dysfunction is observed in heavy [23] and even in some light alcohol consumers [24]. Given that alcohol use is also associated with AF [25] and both AF and alcohol are linked to endothelial dysfunction, it was possible that our findings of no differences in FMD in warfarin and apixaban groups was affected by significantly greater proportion of alcohol consumers and units of alcohol consumed per week in apixaban group.…”
Section: Discussionmentioning
confidence: 88%